Strategi Pengembangan Usaha Mikro di Kota Palembang dengan Pendekatan Analisis SOAR - Yulizar Kasih; Idham Cholid; Charisma Ayu P (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
MSMEs, especially Micro Enterprises, have a strategic role in the Indonesian economy, but on the other hand they still face various problems in their development. This study aims to analyze the development strategy of micro enterprises in Palembang City based on internal and external factors with the SOAR analysis approach (strengths, opportunities, aspirations, results). With a qualitative approach, data from 30 micro enterprises were selected purposively and conveniently and analyzed descriptively using the SOAR analysis approach (SOAR Matrix), IFE Matrix, and EFE Matrix. The findings in this study provide four alternative strategies based on the scores obtained (SO/3.85), (AO/3.80), (SR/3.26), and (AR/3.21). SO and AO strategies are short-term (operational) strategies, while SR and AR strategies are long-term strategies that can be chosen by micro entrepreneurs to develop their businesses. The implications of this study indicate that micro enterprises have a strong enough foundation for business development if operational technical capacity can be improved, then increasing business scale becomes a long-term hope to be achieved.